2004
DOI: 10.1117/12.524532
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive edge detection filter for light stripe projection (LSP) in surface reconstruction

Abstract: The problem of using light stripe projection (LSP) for reconstructing the 3D surface of several objects positioned at different distances from the camera is addressed in this paper. It is shown using LSP for 3D surface reconstruction of objects at different depths can be significantly improved if adaptive edge detection filter is added. The filter is designed as a local dynamic hysteresis thresholding value generator. It adapts knowledge of the wavelet coefficients in a small neighborhood on the row profile an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…It is observed that LSF width function of x coordinates and distance d, expressed in Eq. (18), can properly predict LSF width. Measured LSF width at pixel coordinates (x, y) is shown in Fig.…”
Section: Lsf Width Function Of Distancementioning
confidence: 98%
See 3 more Smart Citations
“…It is observed that LSF width function of x coordinates and distance d, expressed in Eq. (18), can properly predict LSF width. Measured LSF width at pixel coordinates (x, y) is shown in Fig.…”
Section: Lsf Width Function Of Distancementioning
confidence: 98%
“…(18). It is noteworthy that amplitude, x-axis standard deviation, and y-axis standard deviation of Gaussian function are functions of distance d:…”
Section: Lsf Width Function Of Distancementioning
confidence: 99%
See 2 more Smart Citations
“…Curless and Levoy [8] have introduced a new ranging method based on analyzing the time evolution of the structured light reflections to address this problem for a laser stripe range finder. Focus can weaken the stripe information [9].…”
Section: Introductionmentioning
confidence: 99%